Sapiens dictus a sapore. Una Buccolica «grossa» e «sottile» nel Banchetto de’ mal cibati di Giulio Cesare Croce - Luca Vaccaro (DNA Di Nulla Academia)
Poetry, as an «intellectual activity that enjoys its own particular forms», can resort to a collective imagination to depict a specific situation or an objective problem. The reductio ad artem that Giulio Cesare Croce chooses to follow in the comedy of the Banchetto de’ mal cibati (1591) follows the stylistic canons of a poetry-pharmakon that, in preserving the peculiarities of the «theatrical» material of the «Buccolica» theorized by Tomaso Garzoni, welcomes into the connective tissue of a «annoying» diegetic «subject» (the one linked to the «serious infirmities» that occurred in the years 1590 and 1591) two examples of «consolatory cornucopias»: the «anti-cuisine» of the cook Magrino; and the bizarre parody of the Pastor Fido by Battista Guarini, included by Croce in act III, scene 1 of the comedy.